"Lahat para sa lahat" (everything to everybody). Issue 4 (3rd August 2015) - Roanne van Voorst, Dr Ben Wisner, Dr Jörgen Hellman and Dr Gerben Nooteboom, Dr; Bankoff, Greg
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Effective leadership at the grassroots level can make a crucial difference to disaster risk reduction (DRR) at the local level. Guidance, however, is often not provided through the visible structures of local government but through alternative means of articulating power that is no less real and frequently more effective than more formal agencies. The purpose of this paper is to present a biography of one such community leader and his influence in the Philippines and how he is able to foster resilience and reduce risk. These "small men" stand in direct contrast to the more authoritarian, materialistic and reputedly corrupt nature of governance in general. Design/methodology/approach – This paper adopts an historical-sociological approach, utilising archival sources as well as fieldwork to explore the relationship between consensual leadership, social capital and DRR in the Philippines. Findings – Social capital and consensual forms of local leadership have their origin in the challenges posed by daily living in the Philippines. At the grassroots level, Filipino civil society can exhibit a vibrancy, self-reliance and innovation that has not been given proper recognition. In fact, local leadership, social capital and DRR are not unrelated aspects of culture but part of the "mutuality" that exists between people and environment in the archipelago. Originality/value – This paper employs an innovative historical-sociological approach to explore the much maligned and often neglected nature of local unofficial leadership in the Philippines in the context of DRR.